Disentangling magnetic and environmental signatures of sedimentary 10Be/9Be records. (1st April 2021) - Savranskaia, Tatiana; Egli, Ramon; Valet, Jean-Pierre; Bassinot, Franck; Meynadier, Laure; Bourlès, Didier L.; Simon, Quentin; Thouveny, Nicolas
Abstract: Reconstructions of the global production rate of the cosmogenic isotope 10 Be from sedimentary records of authigenic 10 Be/ 9 Be ratios have been successfully used to obtain independent estimates of geomagnetic dipole moment variations caused by field excursions or reversals. In this study, we assess the reliability of 10 Be/ 9 Be as a proxy for the cosmogenic 10 Be production rate by evaluating two potential biasing sources represented by sediment composition and climatic modulation. For this purpose, we compare five high-resolution 10 Be/ 9 Be records of the Matuyama-Brunhes (M-B) field reversal from sediment cores of the Indian, West Pacific, and North Atlantic oceans. Significant increase of 10 Be/ 9 Be ratios at ∼ 774 ka is explained in terms of the dominant control of geomagnetic modulation during the M-B reversal. Results do not support the existence of a direct proportionality between measured sedimentary 10 Be/ 9 Be ratio and cosmogenic 10 Be production rate, as shown by 10 Be/ 9 Be records that offset relative to each other during and outside the M-B reversal. Residual differences between offset-corrected rescaled records do not appear to be related to an incomplete correction of variable sediment scavenging efficiencies by 9 Be normalization. Instead, these differences can be explained by a common climatic modulation model, assuming a linear relation between 10 Be/ 9 Be and the global 10 Be production rate with site- and time-dependent additive and multiplicative coefficients. These coefficients are linear functions of a single global climate proxy identified with the benthic δ 18 O record. Additive coefficients are almost constant in time and can represent up to ∼ 60% of the average 10 Be/ 9 Be value during periods of stable field polarity. Multiplicative coefficients are also site-specific, with mean values representing the bulk scavenging efficiency of the site, and variations about this mean expressing a multiplicative climatic modulation of the 10 Be production rate. The amplitude of this modulation amounts to 10–15% of the maximum variations recorded during the M-B reversal and is sufficiently large to mask minor variations of the dipole moment during stable polarity periods. Reconstructions of the geomagnetic dipole intensity can benefit from the information about climatic modulation effects gained with our modelling approach. Best suited sites for magnetic field reconstructions should be characterized by minimal Be-recycling contributions from ancient 10 Be reservoirs and minimal climatic modulation, as far as it can be determined from relative comparisons with other records. These conditions are most likely encountered in open basins at sites (1) with < 2.8 km water depth, (2) > 200 km offshore, and (3) located underneath a large current system extending over regions with minimum terrigenous inputs. Scaling all records with respect to a chosen reference enables to produce 10 Be/ 9 Be stacks with reduced noise and short-term local environmental effects. Differences between stacks obtained in this manner highlight global climatic effects that need to be considered when generating calibrated reconstructions of the geomagnetic dipole moment. Highlights: 10 Be/ 9 Be marine sedimentary records do not support a direct proportionality with cosmogenic 10 Be production rate. Differences between 10 Be/ 9 Be marine sedimentary records are explained by environmental modulations proportional to benthic δ 18 O. Criteria for the selection of sites with minimal environmental alteration of the sedimentary 10 Be/ 9 Be record are proposed.